Contested Russian tourism : cosmopolitanism, nation, and empire in the nineteenth century - Layton, Susan (Imperial encounters in Russian history., 2021)
"This literary, cultural history examines imperial Russian tourism's entanglement in the vexed issue of cosmopolitanism understood as receptiveness to the foreign and pitted against provinciality and nationalist anxiety about the allure and the influence of Western Europe. The study maps the shift from Enlightenment cosmopolitanism to Byronic cosmopolitanism with special attention to the art pilgrimage abroad. For typically middle-class Russians daunted by the cultural riches of the West, vacationing in the North Caucasus, Georgia, and the Crimea afforded the compensatory opportunity to play colonizer kings and queens in "Asia." Drawing on Anna Karenina and other literary classics, travel writing, journalism, and guidebooks, the investigation engages with current debates in cosmopolitan studies, including the fuzzy paradigm of "colonial cosmopolitanism.""--